Analysis of Head Circumference, Exclusive Breastfeeding, and Child Development at Kedaung Community Health Center - Maharani, Dinda Putri; Shabariah, Rahmini; Rayhana, Rayhana; Farsida, Farsida (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Head circumference is one of the indicators for assessing intracranial volume and brain growth. Development is the improvement of bodily functions and abilities, such as emotional, intellectual, and behavioral development. Breast milk is a source of intake for nutrients for newborns who can support maximum growth and development. Purposes: It is known that the relationship between head circumference and development with the Developmental Pre-Screening Questionnaire (DPsQ) in children aged 3 – 6 months who get breast milk or formula milk in work area of the Kedaung Community Health Center Depok City. Methods: The design is a cross-sectional analytic study with respondents mothers who had a child and got breast milk at least three months after birth. The sampling technique used a convenience sampling method to obtain as many as 50 mothers, and the analysis data was analyzed using statistical methods using the chi-square test. Results: Children with the majority of 3 and 4 months of age were 34% each, female at 52%, breastfeeding alone at 80%, normal head circumference at 98%, and age-appropriate development in general by 90%. There was a significant relationship between head circumference size and breast milk status with DPsQ value and interpretation (p-value=0.002 OR=12.250 CI95%=4.789-31.333); (p-value=0.018 OR=8.143 CI95%=1.144-57.949). Conclusion: There is a 12 times greater relationship between head circumference size and development and an eight times more significant relationship between breast milk status and development in infants aged 3 – 6 months who get breast milk in the work area of the Kedaung Community Health Center Depok City.